Environmental Assessment of Life Cycle of Waste Management System Based on LCAIWM1 Modeling (Case Study: Rasht City) - Kourosh Rahmani; Zeynab Dadashkhah; Morteza Alighadri; Ahmad Mokhtari; Hadi Nazari (Muhandisī-i Bihdāsht-i Muḥīṭ, 2019)
Background: Population growth and increased human activities in urban communities lead to large volumes of waste. This waste volume causes problems for human health and environmental pollution. Recently, a living environment assessment has been developed to improve the situation. The purpose of this study is to compare the environmental impacts of four urban waste disposal scenarios in Rasht city. Methods: In this research, the amount of waste and the data required for logging were first determined and then the four life cycle assessment stages were performed in relation to each of the defined scenarios. Finally, the results were analyzed using the IWM1 model it placed. Results: The results of this study indicate that by disposing of some of the waste in the organic fertilizer plant by composting and landfilling, part of it in the district of sanitary and energy extraction and increasing the recovery rate, we can see a significant reduction in the emission of pollutants was environmental. The ecological index was the best scenario is -2.10E+6 And for the most devastating scenario +2.39E+07 was obtained. Conclusion: According to the environmental assessment and comparison of the results of the life cycle logbook, the first scenario (collection; compost; recycling; landfill) with an ecological index plays an important role in reducing pollution and energy consumption and the title has been chosen as the top management option and has been made available to experts and decision-makers.